2015
DOI: 10.5849/forsci.13-058
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Timber Supply on Public Land in Response to Catastrophic Natural Disturbance: A Principal-Agent Problem

Abstract: Outside MemberManaging public forestland is a challenging enterprise as the government must steward the actions of private forest companies while simultaneously considering public values, natural disturbance, markets, revenue generation and environmental services.Governments use timber sales, volume-based, and area-based tenures to delegate forest harvesting activities to individual timber companies. By delegating forest management, government must wisely navigate the principal-agent relationship to avoid unex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Research by Canadian Forest Service foresters has widely assessed the potential role of Canada's (and even BC's) forests in climate change mitigation (Lemprière et al, 2013;Kurz et al, 2013;Smyth et al, 2014;Xu et al, 2017). The problem is that forest management studies on this scale often ignores economics -the costs of harvesting, slash removal, wildfire suppression, etc., and principal-agent problems when large numbers of stakeholders are involved (see Pyne, 2007;Bogle and Kooten, 2015;Boyland, 2006). It also fails to take into account natural disturbance and how to manage for it in the context of carbon sequestration.…”
Section: Forest Management and Carbon Accountingmentioning
confidence: 99%
“…Research by Canadian Forest Service foresters has widely assessed the potential role of Canada's (and even BC's) forests in climate change mitigation (Lemprière et al, 2013;Kurz et al, 2013;Smyth et al, 2014;Xu et al, 2017). The problem is that forest management studies on this scale often ignores economics -the costs of harvesting, slash removal, wildfire suppression, etc., and principal-agent problems when large numbers of stakeholders are involved (see Pyne, 2007;Bogle and Kooten, 2015;Boyland, 2006). It also fails to take into account natural disturbance and how to manage for it in the context of carbon sequestration.…”
Section: Forest Management and Carbon Accountingmentioning
confidence: 99%
“…Likewise, the tenure system prevents forests from being transferred to other uses, including agriculture, and restricts harvests; it also prescribes certain management practices and imposes fees that might discourage greater use of woody materials for bioenergy (Wang and van Kooten ). In particular, Bogle and van Kooten (, ) found that stumpage fees set by the public landowner (principal) to incentivize greater supply of biomass for energy from mountain pine beetle impacted timber were incompatible with the reality faced by logging companies (agents), thereby leading to a greater mix of unaffected trees in the final harvests.…”
Section: Biomass Electricitymentioning
confidence: 99%